(untitled) (Westerville, O.H., 1986)
The history of technology contextual contrasts: recent trends in the history of technology. Specific examples of high-technology ceramic innovations Egyptian faience: the first high-tech ceramic. Refractories in the ancient and preindustrial world innovation and change in ancient technologies: the anomalous case of the Roman glass industry. Roman concrete and the Roman architectural revolution...
Keywords: Gốm sứ,Ceramics; Hội nghị,Congresses